Acute effects of fatigue to strength and power variables in endurance trained athletes - Vähäkoitti, V. (2015)
The purpose of this bachelor thesis was to investigate how fatigue affects strength and power in endurance trained athletes. This thesis is written for the athletes, coaches and researchers in the field of sport. Total of 7 endurance athletes (age 23.3 years ± 1.3, height 174.7 cm ± 6.4, weight 66.5 kg ± 8.4) volunteered for the study, 4 male and 3 female. Hypotheses were that measured variables do not decrease after fatiguing protocol and that the potentiation may counteract fatigue. Fatigue was induced in a continuous maximal treadmill running, where speed was increased every five minutes by one km/h. When necessary, after 45 minutes of running, speed was increased every minute by one km/h till exhaustion. Strength and power were tested before, during and after running with countermovement jump (CMJ), dynamic leg press power and maximal force of isometric leg press, respectively. Results showed statistical increase in CMJ height at every measurement point, between pre run and 15 min (p = 0.005**), pre run and 30 min (p = 0.009**), pre run and post run (p = 0.033*) and pre run and post 10 (p = 0.049*). Changes in CMJ and lactate did not correlate between each other. Dynamic leg press and isometric leg press results stayed levelled, or increased, but the changes were not statistically significant. Post run heart rate (HR) was 186 (± 5.6) and post run lactate (LA) 11.2 (±1.9), which both demonstrate maximal effort. No changes were found between control and pre run values in any of the strength tests. From these results it can be concluded that maximal running did not induce fatigue in any of the strength measurements. Endurance athletes seems to be fatigue resistant and are able to maintain their strength levels during and after fatigue. Based on prior studies, CMJ results may have increased because of the potentiation in muscles. Data obtained here could be used in developing warm-up, training and competition protocols for endurance athletes.